Nursing actions to prevent infections related to health care in the elderly/Ações de enfermagem frente à prevenção de infecções relacionadas à assistência à saúde em idosos - Manoel Vitório Souza Santana; Cícero Alves da Silva (Universidade Estadual de Alagoas, 2020)
Infection in the hospital is a health problem, where approximately 10% of the patients in the world present after hospitalization, of which 15 to 50% of the patients evolve to death. Considering the nurse as a relevant agent of prevention, the research aims to demonstrate the means of prevention and care provided by nurses to avoid the emergence of Health Care Related Infections in elderly patients using the integrative review of articles, monographs or books from 2014 to 2018 to answer the guiding question: "what are the means of prevention that the nurse uses for elderly clients with risk for nosocomial infection in health care?". A bibliographic integrative review was used in the LILACS and BDENF databases and through the SCIELO virtual library, using the Health Sciences Descriptors: "nursing, prevention, hospital infection, nursing care, infection, the elderly, probes "By adding the boolean" and "in each base search. The result of this study allowed to locate 460 articles related to the topic where only 26 articles were collected and read in full, and six articles were excluded because they did not meet the criteria. From the 20 articles, seven responses were formulated that were discussed and divided in two blocks "general procedures for prevention of hospital infection" and "specific procedures for the prevention of nosocomial infection". The study concluded that nurses should be considered as irreplaceable professionals in the multidisciplinary health team in the face of the means of prevention used, through general and specific prevention measures